Revitalising Industrial Heritage: A Case Study of the Dutch House in Sisak - Mezak, Nina; Paradžik, Elena; Osmanagić, Edvin (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
Sisak, a town with a rich industrial history, situated on three rivers (Sava, Kupa and Oder), has been one of the most important industrial centres in Croatia since the end of the 19th century. The city's industrial heritage has been shaped by various sectors, which have significantly influenced the development of urban and social structures. The Dutch House, a building with a special architecture that today functions as an educational and tourist centre for industrial heritage, stands out as the centre of heritage in Sisak. The renovation project of the Dutch House itself is an example of the successful transformation of an industrial building into a cultural space with various tourist contents. In addition, the Dutch House offers a variety of content such as exhibitions, workshops and multimedia presentations, thus contributing to the preservation of history and the development of cultural tourism in Sisak. Despite challenges such as financial dependence and the seasonality of visits, the Dutch House is an important resource for the promotion of industrial heritage. It is a symbol of a modern approach to preserving the past, enriching Sisak's tourist and cultural offer by creating a deeper connection between visitors and the town's industrial history.